Modern and Belligerent: Entertainment and Pedagogy in Galicia Emigrante's Literary Feuilleton - Garcia-Martinez, Pablo ("Esa luz redentora da noite”. Estudos ofrecidos a Xesús Alonso Montero, 2020)
This article uses as its conducting thread the narrative literature published by the literary feuilleton included in the magazine Galicia Emigrante (1954-1959, 37 numeros), edited by the republican exile Luis Seoane. The text connects the short stories published by the magazine to the efforts for popular education articulated in Galicia Emigrante. At the same time, the text relates this project to those transatlantic Cultural Cold Wars that were refracted, especially during the nineteen-fifties, to the culture organic to Galicianism. Using this framework, the article analyzes the narrative litera-ture published in Galicia Emigrante's literary feuilleton by Antonio Baltar, Eduardo Blanco-Amor, Xose Neira Vilas, Leopoldo Novoa, Xose Nunez Bua, Xose Ruibal, and Ramon de Valenzuela. The article's interest arises, first, from its analysis of narrations that set a precedent for milestones in post-war Galician literature -namely, Non agardei por ninguen (1957) and A Esmorga (1959). Moreover, the text engages with Galician intellectual history from the same period, since it makes visible the project of a third way articulated by the Galicia Emigrante intellectuals, who tried to unsuccessfully affect the debates on the future of a Galician nationalism resisting Francoism, either on exile or, if in Galicia, underground.
CRIS-Team WoS Importer:2021-05-14